2022
DOI: 10.1021/acs.jmedchem.2c01528
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Polymyxins Bearing Reductively Labile Disulfide-Linked Lipids

Abstract: Polymyxins are a class of lipopeptide anti-infective agents with potent and specific activity against Gram-negative bacteria. While toxicity concerns associated with polymyxin B and E (colistin) have historically limited their clinical application, today they are increasingly used as last-resort antibiotics given the rise of multidrug-resistant Gram-negative pathogens. The adverse side effects of polymyxins are well known, particularly as related to their nephrotoxicity. Here, we describe the synthesis and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Our previous investigations involving polymyxin variants containing reductively labile lipids revealed that the incorporation of lipidated d -Cys based building blocks at the N-terminus consistently gave the most active compounds. 26 Also, among the lipids screened in these studies we identified three moieties that were generally associated with potent antibacterial activity: ethylcyclohexyl, isopentyl, and m -chlorobenzyl. In the present study we therefore elected to focus on position 3 analogues wherein the N-terminal moiety was based on d -Cys linked to these three lipids by means of a disulfide bond.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Our previous investigations involving polymyxin variants containing reductively labile lipids revealed that the incorporation of lipidated d -Cys based building blocks at the N-terminus consistently gave the most active compounds. 26 Also, among the lipids screened in these studies we identified three moieties that were generally associated with potent antibacterial activity: ethylcyclohexyl, isopentyl, and m -chlorobenzyl. In the present study we therefore elected to focus on position 3 analogues wherein the N-terminal moiety was based on d -Cys linked to these three lipids by means of a disulfide bond.…”
Section: Resultsmentioning
confidence: 97%
“…The requisite d -Cys lipid-disulfide building blocks were prepared as previously reported. 26 Resin cleavage using mildly acidic conditions yielded protected tripeptides 4a–e , 5a–e , and 6a–e in purities suitable for direct use in the subsequent coupling to PMBH(Boc) 3 3 (Scheme 1C). The solution phase coupling was performed using HCTU/HOBt after which the peptides were fully deprotected by treatment with TFA and purified by RP-HPLC to give 7a–e , 8a–e , and 9a–e .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15,16] In the latter, disulfide-containing linkers are frequently used in targeted drug delivery, which often involve "traceless" self-immolating linkers to be released by thiols in thiol exchange reactions. [15,16,70,71] In such a system, the linker will neither be remaining on the system nor on the cargo after release. In this study, we designed and engineered C. reinhardtii as a biohybrid microbot for the targeted delivery of vancomycin, based on a self-immolative, thiol-mediated release platform.…”
Section: Introductionmentioning
confidence: 99%
“…A complementary approach utilizes endogenous stimuli such as the pH value or redox homeostasis [15,16] . In the latter, disulfide‐containing linkers are frequently used in targeted drug delivery, which often involve “traceless” self‐immolating linkers to be released by thiols in thiol exchange reactions [15,16,70,71] . In such a system, the linker will neither be remaining on the system nor on the cargo after release.…”
Section: Introductionmentioning
confidence: 99%